Levels of circulating Fibroblast Growth Factor 23 (FGF23) and prognosis in cancer patients with bone metastases - Mansinho, André (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).